Being a Pioneer : A Case of Intention, Market, and Challenges - Mohapatra, Soumya; Rath, Adarsh; Kar, Brajaballav (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : An individual who completes engineering in his/her heydays, works for the government at a lucrative position, quits his/her job to pursue higher education abroad, refuses jobs abroad, comes back and joins a private organization in his/her own state, is less likely to be an entrepreneur. What are some challenges pioneer entrepreneurs face to establish and run their organization is important to understand. The influence of different contexts also assumes importance. The purpose of this article was to understand entrepreneurial processes and decisions from a particular entrepreneur in a specific context. Methodology : In order to comprehend the experiences of the entrepreneur regarding the historical background, traits, and life path and learning of an entrepreneur, this study employed a narrative technique of inquiry. The theory and existing research literature have been compared with the individual experiences of entrepreneurs. Findings : Entrepreneurship is influenced by push variables such as political backdrop, high self-efficacy, networking, and job unhappiness. The goal of entrepreneurship is to be supported by opportunities for success, industry networks, peer networks, and prevailing policies. Policies that encourage entrepreneurship and are simple to understand and apply could increase compliance; nevertheless, a loose policy could lead to abuse and corruption. Practical Implications : In the form of a case study, narrative research could be used to practically illustrate a situation, decision-making process, result, and implication. Policymakers, educators, and entrepreneurs could use the knowledge in their respective sectors. Originality : While distinct, narrative research is not broadly applicable, it is crucial to comprehend particular case findings in order to comprehend the order of decisions and their results. The case study’s general lessons and ability to make sense of things were retained.